DECADAL-SCALE DYNAMICS OF WATER, CARBON AND NITROGEN IN A CALIFORNIA CHAPARRAL ECOSYSTEM: DAYCENT MODELING RESULTS - Li X.; Meixner T.; Sickman Ja.O.; Miller A.E.; Schimel J.P.; Melack J.M. (My University, 2006)
The Mediterranean climate, with its characteristic of dry summers and wet winters, influences the hydrologic and microbial processes that control carbon (C) and nitrogen (N) biogeochemical processes in chaparral ecosystems. These biogeochemical processes in turn determine N cycling under chronic N deposition. In order to examine connections between climate and N dynamics, we quantified decadal-scale water, C and N states and fluxes at annual, monthly and daily time steps for a California chaparral ecosystem in the Sierra Nevada using the DAYCENT model. The daily output simulations of net mineralization, stream flow and stream nitrate (NO3−) export were developed for DAYCENT in order to simulate the N dynamics most appropriate for the abrupt rewetting events characteristic of Mediterranean chaparral ecosystems. Overall, the magnitude of annual modeled net N mineralization, soil and plant biomass C and N, nitrate export and gaseous N emission agreed with those of observations. Gaseous N emission was a major N loss pathway in chaparral ecosystems, in which nitric oxide (NO) is the dominant species. The modeled C and N fluxes of net primary production (NPP), N uptake and N mineralization, NO3− export and gaseous N emission showed both high inter-annual and intra-annual variability. Our simulations also showed dramatic fire effects on NPP, N uptake, N mineralization and gaseous N emission for three years of postfire. The decease in simulated soil organic C and N storages was not dramatic, but lasted a longer time. For the seasonal pattern, the predicted C and N fluxes were greatest during December to March, and lowest in the summer. The model predictions suggested that an increase in the N deposition rate would increase N losses through gaseous N emission and stream N export in the chaparral ecosystems of the Sierra Nevada due to changes in N saturation status. The model predictions could not capture stream NO3− export during most rewetting events suggesting that a dry-rewetting mechanism representing the increase in N mineralization following soil wetting needs to be incorporated into biogeochemical models of semi-arid ecosystems.
Keywords: CARBON AND NITROGEN CYCLING; CHAPARRAL ECOSYSTEM; DAYCENT; DRYING-REWETTING PULSE; FIRE DISTURBANCE; MEDITERRANEAN-CLIMATE; NITROGEN DEPOSITION